Ethanol-Induced Hypothermia and Clearance Curve Across the Ages - Matthews, Douglas; Kastner, Abigail; Schneider, Amelia; Benes, Ashley; Scaletty, Samantha; James, Kimberly; Watson, Meredith (My University, 2018)
By the year 2030, 20% of the US population will be over the age of 65 providing a potential strain to the health care system (U.S. Census Bureau). A large segment of older individuals consume alcohol at dangerous levels with up to 3% meeting the diagnostic criteria for an alcohol use disorder. Interestingly, 33% of the elderly with an alcohol use disorder did not begin risky drinking until later in life, often following a major life change. These individuals have been termed Type 1 alcoholics. Little is known about the consequences of chronic alcohol use in later life due to few animal studies investigating alcohol in aged rats. Previous research has shown that adolescent and adult rats have significantly different patterns of ethanol-induced hypothermia that varied by dose (Ristuccia & Spear, 2008). The current experiment investigates the effect of chronic intermittent ethanol on hypothermia and aging by assessing adolescent, adult, and aged rats following ethanol injection.
Color poster with text and graphs.
Keywords: Posters; Hypothermia; Alcoholism; Seniors